Problems and prospects of algorithmic trade in financial markets - B. V. Batiuk (Путеводитель предпринимателя)
The use of algorithms in trading (algorithmic trading) is the trend of recent decades, which has largely changed the market. As part of the research, the fundamentals of algorithmic trading, it’s possible application during exchange trading, were examined in detail. An assessment was also made of the accessibility of obtaining exchange robots for the corporate sector, the benefits of use and optimal conditions for use. Moreover, the impact of exchange trading on the global economy is valuable and a forecast is made for the further development of trading robots.